PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, LINGKUNGAN KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN BANKALTIMTARA - Zulfikar Zulfikar; Diyah Permana; Ayu Arvina Anwar (Politeknik Negeri Samarinda, 2020)
This study aims to analyze work discipline, work motivation, work environment, and leadership on the performance of Bankaltimtara employees. The study population was employees of the Bankaltimtara head office in Samarinda. The sample in this study were 80 employee respondents. The analytical tool used in this study is multiple regression analysis. The results of this study, based on simultaneous tests proved that work discipline, motivation, work environment, and leadership significantly influence the performance of Bankaltimtara employees. Similarly, partially, work discipline, work motivation, and work environment significantly influence, but leadership does not significantly influence the performance of Bankaltimtara employees. Keywords: work discipline, work motivation, work environment, leadership, employee performance.